2022
DOI: 10.1136/gutjnl-2021-326563
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition is associated with SARS-CoV-2 vaccine immunogenicity and adverse events

Abstract: ObjectiveThe gut microbiota plays a key role in modulating host immune response. We conducted a prospective, observational study to examine gut microbiota composition in association with immune responses and adverse events in adults who have received the inactivated vaccine (CoronaVac; Sinovac) or the mRNA vaccine (BNT162b2; BioNTech; Comirnaty).DesignWe performed shotgun metagenomic sequencing in stool samples of 138 COVID-19 vaccinees (37 CoronaVac and 101 BNT162b2 vaccinees) collected at baseline and 1 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
143
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(159 citation statements)
references
References 54 publications
(81 reference statements)
14
143
2
Order By: Relevance
“… 28 Previous studies have revealed that multimorbidity does not translate to an additional risk of adverse events after COVID-19 vaccination 29 and that the composition of the gut microbiota might contribute to differences in post-vaccination adverse event rates. 30 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Previous studies have revealed that multimorbidity does not translate to an additional risk of adverse events after COVID-19 vaccination 29 and that the composition of the gut microbiota might contribute to differences in post-vaccination adverse event rates. 30 …”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic effect of probiotics in fighting against influenza virus and other kinds of coronavirus have been estimated, and its role in COVID-19 is awaited from many ongoing clinical trials ( Kurian et al, 2021 ). Tun’s study has identified specific gut microbiota markers associated with improved immune response and reduced adverse events following COVID-19 vaccines ( Ng et al, 2022 ). In our study, the diversity analyses of the gut microbiome reveal that Moraxella osloensis , Roseomonas sp., and uncultured bacteria Oscillospira , Lachnospiraceae , and Nitrospira , Burkholderiaceae were the primary difference between the recombinant yeast and negative control group ( p < 0.05, Meta Stats).…”
Section: Discussionmentioning
confidence: 99%
“…For the inactivated vaccine (CoronaVac), the enrichment of B. adolescentis and carbohydrate metabolismrelated pathways were associated with higher antibody response. For the mRNA vaccine (BNT162b2), the abundance of bacteria with flagella and fimbriae in the baseline gut microbiota was positively associated with higher antibody responses (Ng et al, 2022b). Additionally, animal experiments confirmed the potential of use the oral probiotic strain Lactobacillus plantarum GUANKE in enhancing the specific humoral and cellular immune responses of SARS-CoV-2 vaccines (Xu J. et al, 2021).…”
Section: Covid-19 Vaccinementioning
confidence: 81%